NILAI-NILAI PENDIDIKAN KARAKTER DALAM AL-QUR’AN SURAH LUQMAN AYAT 12-19 (Studi Tafsir Al-Misbah) - Meli Meli (Scolae: Journal of Pedagogy, 2019)
The formulation of the values of character education in the Qur'an Surah Luqman verses 12-19 basically includes threefundamental education, namely: faith education in verses 12,13 and 15, shari'ah education in verses 14, 15, and 17, andmoral education in paragraphs 14, 15, 16,18, and 19. Character education in Surah Luqman includes the command amarma'ruf nahi mungkar, and this exemplaryness is very relevant to the 18 values of nation's character education whichcontain disciplinary characters. Discipline is an example that must be internalized to every individual as Luqman ingiving lessons to his son in terms of worship properly and correctly and on time.The realization of karakrater education makes the formation of Islamic personality as an option in order to fortifychildren as early as possible from negative environmental influences. The formation of children's personality is inprinciple an ongoing process. The role of various parties, especially parents in realizing sustainable character educationby establishing good communication and cooperation between parents and schools in educating must use theappropriate strategies and methods in accordance with the times.